Which Rights are Right? Water Rights, Culture, and Underlying Values - Pradhan, Rajendra; Meinzen-Dick, Ruth (Water Nepal, 2003)
Over the past decade there has been increasing alarm worldwide about water scarcity, which, it is feared, will lead to massive malnutrition and famines, thirst, and unhygienic dwelling conditions as well as to violent clashes among different users and even wars between nations. Consequently, as a way of mitigating possible conflicts over increasingly scarce water resources there has been increased attention on clarifying what water rights entail. This in itself has raised another conflict: a conflict over the way in which water rights are defined. Much of the international debate has posed the issue as a simple dichotomy between economic efficiency and basic welfare or human rights. A closer look at the multiple forms of water rights derived from state, customary, local, and religious laws, however, reveals more complexity in the principles and values underlying how rights are defined, both in terms of abstract and specific situations as well as in terms of how they are actualised or put into practice by different parties. Both water rights and the laws from which they are derived are linked to wider cultural meanings and values associated with water and notions about what are fair and just or equitable. Often, several laws and notions of equity coexist and interact in a given social field, such as a community, village, or nation state. There may, for example, be a different constellation of rights and different notions of equity concerning drinking water than concurring irrigation or environmental uses. Therefore, when discussing water rights, it is important not to speak of water in general but to disaggregate water uses and water property regimes; only thus will we understand the plurality of values, meanings and notions of equity attached to water. This paper discusses the links between water rights and the broader meanings, values, and notions of equity attached to water, as reflected in state local laws and selected religious laws. Different conglomerations of rights to water (understood broadly to include both rights to use and rights to control or make decisions) for different uses and in different water (property) rights regimes are examined. More specifically, the state laws of selected Western and non-Western countries; Hindu, Muslim and Christian laws (especially those relating to drinking water); and several local or customary laws dealing with water are discussed. The paper argues that, rather than seeking a single, hegemonic type of water law or valuation of water, recognizing the pluralistic legal frameworks, types of rights, and meanings of water is not only a more realistic viewpoint, but also one which can lead to more productive negotiations over water rights and water use. Water Nepal Vol. Vol.9-10, No.1-2, 2003, pp.37-61